Cryoprotective characteristics of different sugar alcohols on peeled Pacific white shrimp (Litopenaeus vannamei) during frozen storage and their possible mechanisms of action. Issue 1 (1st January 2020) - Zhang, Bin; Yao, Hui; Qi, He; Ying, Xiao-guo
ABSTRACT: Sugar alcohols, also known as polyols, have been widely applied in food products for their unique properties. In this work, the effect of soaking treatments composed of the sugar alcohols xylitol, sorbitol, erythritol, lactitol, mannitol, maltitol, and isomaltitol on the quality properties of peeled Pacific white shrimp during frozen storage were evaluated. Samples treated with water and sodium pyrophosphate (Na4 P2 O7 ) were designated as the negative and positive controls, respectively. The results indicated that significant improvements were found in thawing, pressing, and cooking loss, myofibrillar protein content, myofibrillar Ca 2+ -ATPase activity, and textural variables in xylitol- and mannitol-treated shrimp as compared to that of control samples. Water mobility analyses showed that xylitol and mannitol effectively increased the relaxation times T 21 and T 22 and the percentage of A 21 (trapped water) but decreased the percentage of A 22 (free water) in muscle tissue. Additionally, the microstructural results indicated that soaking in xylitol and mannitol significantly slowed the damage caused to muscle tissues by large ice crystals. Here, the incorporated xylitol and mannitol molecules presumably replaced water molecules by forming large hydrogen bonds with the muscle proteins, thereby stabilizing their structures in the absence of water while in the frozen state and suppressing the destruction of tissue structure. To note, the lactitol, isomaltitol, and maltitol used in this study did not seem to significantly contribute to cryoprotective effects on shrimp muscle during the experimental period.